Law Implementation of Cybercrime in Indonesia - I Nyoman Sukayasa; Wayan Suryathi (Politeknik Negeri Bali, 2018)
Cybercrime is a criminal act that is prohibited by every country in the world. Cybercrime cases have occurred and gave negative impacts on Indonesian computer users. This study explains that common cybercrime patterns consist of cracking, carding, twitter hijacking, cybersquatting, use of someone else's account, identity theft or data leakage, data forgery, online probing and port scanning, sabotage and extortion, against government and against property, and virus attacks. This research uses qualitative descriptive approach, with statute approach analysis technique and empirical juridical method. Data collection was done through document studies on articles and case reports in Indonesia. The patterns and forms of cybercrime in Indonesia are stated in articles 27 to 35 of Law Number 11/2008. The criminal act against cybercrime applies chapter 45 to article 52 of Law Number 11/2008. The application of the legal basis of cybercrime cases that has occurred in Indonesia is subject to articles 263, 362, 363, 378, 282 paragraph 1 of the Criminal Code, articles 29 and 56 UURI Number 44/2008, article 8 and 303 of Law Number 7/1974.